Peran Perbankan Syariah terhadap Pertumbuhan Ekonomi Indonesia - Safaah Restuning Hayati (JURNAL INDO-ISLAMIKA, 2014)
The paper analyzes the role of Islamic banking for economic growth in Indonesia. The rapid development of Islamic banking in the country followed the economic growth was the research basis of the paper. The analysis in this paper uses Ordinary Least Square method to determine how much Islamic banking influenced the growth represented by Gross Domestic Product (GDP). The result of regression model testing found that the total assets of Islamic banking had no significant effect (negative) on GDP, while the Islamic banking financing process had significant process had significant effect (positive) on GDP. Variable total assets and total financing of Islamic banking are able to explain the effect 33.8% of GDP variable. This means that Islamic banking has a very small role related to economic growth in Indonesia. The research indicates that the solution for increasing for the influence of Islamic banking could include increasing market share and increasing the share of muḍârabah financing schemes, strengthening regulation, improving the quality and quantity of human resources, and adapting technological advances.